2014
DOI: 10.1113/jphysiol.2014.276683
|View full text |Cite
|
Sign up to set email alerts
|

Human lymphatic vessel contractile activity is inhibited in vitro but not in vivo by the calcium channel blocker nifedipine

Abstract: Key pointsr We studied the effects of antihypertensive calcium channel blockers on Ca V 1.2, the predominantly expressed L-type calcium channel in the largest human lymphatic vessel, the thoracic duct.r Human lymphatic collecting vessels, both large and small, are highly-sensitive in vitro to calcium channel blockers; exposure to these drugs inhibits endogenous lymphatic contractile activity and action potentials and diminishes noradrenaline-induced phasic contractions.r In vivo administration of calcium chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 57 publications
3
52
0
Order By: Relevance
“…16,17 Our observations confirm that sarcolemmal Ca 2 + entry via L-type Ca 2 + channels contributes to the spontaneous Ca 2 + transients that precede lymphatic phasic contractions. Studies on mesenteric lymphatic vessels using wire myograph have shown that nifedipine in rats (10 -6 M) 16 and in humans (3 · 10 -9 M) 33 abolishes lymphatic pumping. Our findings with the lymphatic vessels isolated from rats that did not receive alcohol reflect the results of Atchison and Johnston, who used isolated bovine mesenteric lymphatic vessels and observed that nifedipine, applied at the same concentration we used, decreased both contraction frequency and amplitude of contraction.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Our observations confirm that sarcolemmal Ca 2 + entry via L-type Ca 2 + channels contributes to the spontaneous Ca 2 + transients that precede lymphatic phasic contractions. Studies on mesenteric lymphatic vessels using wire myograph have shown that nifedipine in rats (10 -6 M) 16 and in humans (3 · 10 -9 M) 33 abolishes lymphatic pumping. Our findings with the lymphatic vessels isolated from rats that did not receive alcohol reflect the results of Atchison and Johnston, who used isolated bovine mesenteric lymphatic vessels and observed that nifedipine, applied at the same concentration we used, decreased both contraction frequency and amplitude of contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Using Tetrodotoxin (TTX), fast Na + channel inward current was shown to significantly contribute to the spontaneous action potentials initially in sheep mesenteric collecting lymphatics (445), and later in human mesenteric collecting lymphatics and thoracic duct, with Na v 1.3 as the predominantly expressed voltage-sensitive Na + channel (1062). However, in both humans and sheep there are some vessels that are resistant to TTX, in which voltage-gated Ca 2+ channels may be sufficient to produce action potentials (445, 1062), as blockade of L-type voltage-gated Ca 2+ channels can eliminate action potentials in collecting lymphatic vessels (1064, 1112). In bovine and guinea pig lymphatic vessels, TTX has not been found to block spontaneous contractions (47, 676, 1104).…”
Section: Lymphangions and The Lymphatic Pump Mechanismmentioning
confidence: 99%
“…The fast, initial repolarization may be due to an outward current caused by activation of K v channels (1061). L-type voltage-gated Ca 2+ channels, which open more slowly than the fast voltage-gated Na + channels, contribute to the plateau phase of cardiac action potentials, and are suspected to contribute to the depolarization and plateau phase in lymphatic smooth muscle (445, 1064). Recent work shows that the L-type voltage-gated Ca 2+ channel isoform Ca v 1.2 is expressed in lymphatic smooth muscle from rats (595) and humans (1064).…”
Section: Lymphangions and The Lymphatic Pump Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…LMC contractions depend predominantly on Ca 2+ influx through L‐type, voltage‐gated Ca 2+ channels (Telinius et al . c ), while the resting membrane potential is influenced substantially by Cl − (van Helden, ; von der Weid et al . b ) and voltage‐gated K + channels (Allen & McHale, ; Telinius et al .…”
Section: Normal Lymphatic Pumpingmentioning
confidence: 99%